Integration of Pancasila Values and Islamic Teachings in Building National Character in the Digital Age - Khaerunnisa; Adelia Sasmira; Muhammadong (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The digital era has brought major transformations in various aspects of life, including in the formation of the nation's character. Although it offers convenience and innovation, this era also presents serious challenges, such as moral crisis, the spread of disinformation, degradation of social values, and weakening of national identity. In the midst of these conditions, the integration of Pancasila values and Islamic teachings is a relevant strategic approach to strengthen the character and identity of the Indonesian nation. Both have aligned values that cover spiritual, social, and humanitarian aspects that can be implemented contextually in education, social life, and the digital space. This article discusses how the integration of Pancasila values and the principles of Islamic teachings can form a strong national character in the digital era, as well as its implementation strategies through character education, moral digital literacy, and role models in public spaces. This qualitative research uses a literature study methodology to explore various sources, including research journals and policy documents. Data were analyzed using content analysis, focusing on themes related to the values of Pancasila and Islamic teachings and their integration in building character in the digital era. The findings emphasize the importance of integrating Pancasila values and Islamic teachings from an early age that are in line with the development of national character amid the challenges and opportunities of the digital era.